Adrenocortical carcinoma (ACC) with massive liver metastases in a 4-year-old female patient: the significance of chemotherapy and imaging studies in treatment and diagnosis – a case report - Głaz, Aneta; Wach, Damian; Mitek-Palusińska, Joanna; Woźniak, Magdalena (Journal of Education, Health and Sport, 2023)
Background: Adrenocortical carcinoma (ACC) is a retroperitoneal tumour, accounting for less than 0.2% of all malignancies in children. In pediatric patients, the most common clinical presentation is virilisation, either isolated or in combination with hypercortisolemia. Case report: A 4-year-old girl was admitted to the hospital for diagnostic evaluation of precocious puberty and features of hypercorticism. Ultrasonography revealed a heterogeneous neoplastic lesion between the left kidney and spleen. Computed tomography (CT) scan confirmed a pathological mass in the left adrenal region. The urine steroid profile was suggestive of adrenocortical carcinoma. The patient was qualified for surgery. Histopathological examination confirmed the diagnosis. A PET scan performed a few months later showed a metabolically active lesion in the left lobe of the liver. Due to the suspicion of a metastatic focus, it was proposed to implement systemic treatment, to which the patient's parents did not agree. After 15 months of no treatment and oncological follow-up, the girl was referred to the ED with symptoms of progression of the neoplastic process. In the face of a renewed lack of consent to the inclusion of treatment, the patient was referred to a home hospice, where she died a short time later. Conclusions: In the pediatric population, adrenocortical carcinoma is a rare neoplasm with a very poor prognosis. Prompt diagnosis enables early identification of the primary tumour and implementation of appropriate treatment. Imaging examinations are crucial in order to assess the size of the tumour, the extent of local invasion and the presence of potential metastases.